Mozambique Jobs Diagnostic Volume 2 - Jobs Strategy Policy Note - Lachler, Ulrich (The World Bank, 2021)
Mozambique is about to face two transformative opportunities for accelerating the pace of poverty reduction: the prospect of major resource inflows from the extraction of liquid natural gas (LNG) and other minerals, and the prospect of a significant demographic dividend. But to take advantage of these transformative opportunities, however, Mozambican policy makers will have to overcome several important challenges: it will be necessary to accelerate Mozambique's structural transformation, both in sectoral and job quality terms. Achieving a faster jobs transformation in the context of an extractives resource-driven economic model and capturing the demographic dividend of an expanding population are the key jobs outcomes at the basis of this Jobs Strategy Note, which rests on five pillars defined by the broad jobs' challenges outlined, together with the overarching challenge of maintaining a stable macroeconomic and governance framework. While a successful sectoral transition from agriculture to non-agriculture largely depends on developments across markets and sectors, a successful job transition has more to do with factors affecting the functioning of the labor market. Although the ultimate objective is to achieve a successful transition to nonagricultural, wage-based employment, there is still considerable room for improving overall productivity and job quality in the informal and agricultural sectors